Allogeneic cord blood transfusions prevent fetal haemoglobin depletion in preterm neonates. Results of the CB‐TrIP study. (8th June 2020) - Teofili, Luciana; Papacci, Patrizia; Orlando, Nicoletta; Bianchi, Maria; Molisso, Anna; Purcaro, Velia; Valentini, Caterina Giovanna; Giannantonio, Carmen; Serrao, Francesca; Chiusolo, Patrizia; Nicolotti, Nicola; Pellegrino, Claudio; et al.
Summary: Repeated red blood cell (RBC) transfusions in preterm neonates are associated with poor outcome and increased risk for prematurity‐associated diseases. RBC transfusions cause the progressive replacement of fetal haemoglobin (HbF) by adult haemoglobin (HbA). We monitored HbF levels in 25 preterm neonates until 36 weeks of post‐menstrual age (PMA); patients received RBC units from allogeneic cord blood (cord‐RBCs) or from adult donors (adult‐RBCs), depending on whether cord‐RBCs were available. Primary outcome was HbF level at PMA of 32 weeks. Twenty‐three neonates survived until this age: 14 received no transfusions, two only cord‐RBCs, three only adult‐RBCs and four both RBC types. HbF levels in neonates transfused with cord‐RBCs were significantly higher than in neonates receiving adult‐RBCs ( P  < 0·0001) or both RBC types ( P  < 0·0001). Superimposable results were obtained at PMA of 36 weeks. Every adult‐RBCs transfusion increased the risk for an HbF in the lowest quartile by about 10‐fold, whereas this effect was not evident if combined adult‐ and cord‐RBCs were evaluated. Overall, these data show that transfusing cord‐RBCs can limit the HbF depletion caused by conventional RBC transfusions. Transfusing cord blood warrants investigation in randomised trials as a strategy to mitigate the severity of retinopathy of prematurity (NCT03764813).